Genetic responses in milling, flour quality, and wheat sensitivity traits to grain yield improvement in U.S. hard winter wheat. (May 2020) - Van der Laan, Liza; Goad, Carla L.; Tilley, Michael; Davila-El Rassi, Guadalupe; Blakey, Adrienne M.; Rayas-Duarte, Patricia; Hunger, Robert M.; de Oliveira Silva, Amanda; Carver, Brett F.
Abstract: A rising global population necessitates continued genetic improvement of wheat ( Triticum spp. ), but not without monitoring of unintended consequences to processors and consumers. Our objectives were to re-establish trends of genetic progress in agronomic and milling traits using a generational meter stick as the timeline rather than cultivar release date, and to measure correlated responses in flour quality and human wheat-sensitivity indicators. Grain yield and kernel size showed stepwise increases over cycles, whereas wheat protein content decreased by 1.1 g/100 g. Reduced protein content, however, did not result in lower dough strength pertinent to bread baking. A novel method of directly testing gluten elasticity via the compression-recovery test indicated a general increase in gluten strength, whereas the ratio of total polymeric to total monomeric proteins remained stable. Also showing no change with genetic progress in yield were flour levels of gluten epitopes within the key immunotoxic 33-mer peptide. The oligosaccharide fructan, present in milled and wholemeal flours, increased with increasing grain yield potential. While yield improvement in U.S. bread wheat was not accompanied by a decline in gluten strength or systematic shift in a key wheat sensitivity parameter, the unanticipated rise in total fructans does implicate potentially new dietary concerns. Graphical abstract: Six breeding cycles of yield improvement in U.S. bread wheat and indirect selection responses in potential immunogenicity and total fructans in milled flour. Image 1 Highlights: Increases in bread wheat grain yield do not associate with loss in dough strength. Increasing wheat yield causes no movement in flour immunoactivity level. Cyclic rise in flour fructans with increasing grain yield may shift dietary concerns.